2016
DOI: 10.1176/appi.ps.201500424
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Primary Care Into Community Mental Health Centers: Impact on Utilization and Costs of Health Care

Abstract: Investments in PBHCI can improve access to outpatient medical care for persons with severe mental illness and may also curb hospitalizations and associated costs in more established programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 17 publications
6
45
1
Order By: Relevance
“…Implementation of PBHCI in settings with lower starting points may achieve contrasting results. In addition, only two years of follow-up data were available for the wave 2 clinics, while previous have suggested that the impact of integrated programs may take additional time to occur (Krupski et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementation of PBHCI in settings with lower starting points may achieve contrasting results. In addition, only two years of follow-up data were available for the wave 2 clinics, while previous have suggested that the impact of integrated programs may take additional time to occur (Krupski et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…A study of two PBHCI programs in Washington State compared inpatient and outpatient utilization by patients enrolled in the program with that received by patients seen in the same clinic who did not enroll. Although the study found that PBHCI increased utilization of outpatient physical health services, data used in the study were limited to care received from providers who were affiliated with the PBHCI site (Krupski et al, 2016). More comprehensive data on utilization are needed to determine whether additional care was received from external providers or whether care previously received from external providers was simply shifted to the PBHCI clinic.…”
Section: Introductionmentioning
confidence: 99%
“…28,35,36 Krupski and colleagues found reduced all-cause hospitalizations in an established BHH program but not a newer one, and no BHH impact on ED use. 28 Evaluation of the Health Home demonstration in Missouri (while not solely a BHH intervention) showed reduced hospitalizations and ED use among enrollees. Service use reductions occurred after only one year, inclusive of a lengthy ramp-up period, and as Krupski et.…”
Section: Discussionmentioning
confidence: 99%
“…12,25,26 Yet the effectiveness of BHH models remains in question. Studies to date have applied the BHH in unique settings such as the Veteran’s Health Administration, 20,27 examined varied BHH intervention components, 23 included diagnostically heterogeneous populations, 23,28 or focused primarily on physical health outcomes. 28 Even evaluations that specified intervention components have yielded mixed findings, such as improvements in quality measures but not clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation